Why Enroll in a Graduate-level Vocational Education Program?: Exploring Views of Graduate Students Using Latent Dirichlet Allocation Topic Modelling - Tejero, Ma Zosima Labro (Jurnal Pendidikan Progresif, 2023)
Objectives: The main objective of this study was to identify the most frequent words, the sentiment, and the underlying themes in the students' responses regarding their enrollment in a graduate-level vocational education program. Methods: Word Cloud generation, VADER Sentiment Analysis and Latent Dirichlet Topic modelling were utilized to analyze the collected data. Findings: The most frequent words in the responses of students were "promotion", "personal", "development", "future", "possible", "knowledge", and "career". The sentiment analysis showed a positive overall polarity of 0.477 with no negative sentiment. The themes that emerged from the analysis were the desire for increased knowledge in vocational education, the requirement for a graduate degree, and the desire for career promotion. The findings provide insights into the needs and expectations of students and can be used by institutions to design programs and improve the educational experience of students. Keywords: vocational, sentiment analysis, graduate level, topic modelling, themes.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202337